An Evaluation of Different Materials for Surface Treatment on Microleakage of Repaired Composite Resin Restoration - Jabbar H Kammel; Emad F Alkhalidi (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate the effect of different surface treatment on the microleakage of repaired CI V com-posite resin restoration. Materials and methods: This study was performed in vitro on 20 caries free premolar teeth. Standardized class V cavity preparation on buccal and lingual surfaces of each tooth was done, forty cavities cleaned with distilled water and dried, then the cavities were filled with the composite. After that, all teeth were stored in normal saline for 3 months, so that the filling become old then remove 1mm of composite from all cavities. The cavities were divided into four groups. The first two groups were treated with 37% phosphoric acid. The other groups treated with 9% hydrofluoric acid the groups II and IV were treated with silane coupling agent, then all cavities were filled with compo-site after 5th generation bonding agent were applied .The teeth were stored for one week after that the Samples were thermocycled and immersed in methylene blue dye, The samples were sectioned, and examined using stereomicroscope. Results: Samples treated with silane coupling agent showed less microleakage than those without silanation. There was highly significant difference between samples acid etched using hydrofluoric acid with those etched with phosphoric acid. Conclusions: Silane coupling agent and the hydrofluoric acid significantly decreased microleakage of repaired CI V compo-site resin restoration.